Dietary nutrient intake and cancer presence: evidence from a cross-sectional study - Qin, Youjia; Chen, Liu; Zhao, Zilong; Li, Yuguan; Tian, Xuan; Feng, Mingqian; Tang, Jing; Ji, Kangkang (Frontiers in Nutrition, 2025)
BackgroundWhile the role of specific nutrients in cancer is established, associations between comprehensive between dietary nutrient intake and cancer presence remain underexplored. This cross-sectional study investigates global dietary nutrient profiles in relation to solid and blood cancers.MethodsA total of 42,732 mobile adults from the National Health and Nutrition Examination Survey (NHANES, 2001–2023) were enrolled in this study. The potential associations of dietary intakes of 34 nutrients and 4 common trace components with cancer presence were investigated by weighted logistic regression and restricted cubic spline.ResultsHigher intake of saturated fatty acid (OR = 1.1082, 95% CI: 1.0110–1.2146), β-carotene (OR = 1.0431, 1.0096–1.0777) and vitamin K (OR = 1.0370, 1.0094–1.0654) was positively associated with overall cancer presence, while phosphorus intake (OR = 0.9016, 0.8218–0.9892) showed a protective association. For solid tumors, dietary intakes of saturated fatty acid (OR = 1.1099), α-carotene (OR = 1.0353), β-carotene (OR = 1.0484), and vitamin K (OR = 1.0405) exhibited positive associations. Retinol intake was linked to blood carcinoma (OR = 1.0935, 1.0222–1.1698). Dose–response analyses revealed linear relationships without non-linear thresholds.ConclusionSpecific dietary nutrients, notably saturated fats, carotenoids, and vitamin K, are associated with increased cancer presence, whereas phosphorus intake is associated with the reduced cancer presence. Due to the cross-sectional nature of the study and the measurement of dietary intake after cancer diagnosis, a causal relationship could not be established. These findings underscore the need for longitudinal studies to establish causality and inform dietary interventions in cancer management.